A Comprehensive Review of Complex Regional Pain Syndrome: Diagnostic Challenges and Therapeutic Innovations - Nur Azza, Kamala Kan; Mahmud, Mahmud; Susianti, Noor Alia; Widyastuti, Yunita; Puspitasari, Ika; Nathania, Caroline Evanthe (Faculty of Medicine, Brawijaya University, 2026)
Complex regional pain syndrome (CRPS) is a medical condition marked by disturbances in motor, sensory, and autonomic functions in the affected extremities, which may occur with or without trauma. The prevalence of CRPS is approximately 2–5% in adults, with a higher incidence in females. Annually, CRPS affects between 5.4 and 26.2 individuals per 100,000 population. The diagnosis of CRPS presents a significant clinical challenge, as its symptoms often mimic those of other conditions, frequently leading to misdiagnosis. A thorough understanding of CRPS and its diagnostic criteria is crucial for clinicians, as accurate diagnosis directly affects treatment selection and outcomes. An effective management approach should encompass the four foundational pillars of CRPS therapy, i.e., education and information for the patients, pain management including both pharmacologic and pain intervention approaches, vocational and physical rehabilitation, and psychological interventions. A comprehensive and individualized treatment strategy is crucial to achieving optimal outcomes. When inadequately treated, CRPS can have profound effects on the physical, emotional, social, and quality-of-life (QoL) aspects, as well as the financial well-being, of both patients and their families. Given the relatively high prevalence of CRPS, the diagnostic complexity, and the broad implications for patient care and QoL, a thorough review of the existing knowledge and treatment strategies for CRPS is warranted. This review aims to provide clinicians with the latest information on diagnosing and managing CRPS, thereby supporting timely and effective clinical decision-making. Accurate diagnosis and appropriate therapy are expected to yield positive outcomes for the patients and their families.